Muscle Energy Technique dan Micro Wave Diathermy untuk Menurunkan Nyeri pada Low Back Pain - Aco Tang; Muh Thahir; Hasbiah Hasbiah (FORIKES, 2022)
Low back pain is pain that is felt in the lower back area, which can be local pain or radicular pain or both. This study aims to determine the effect of muscle energy technique and microwave diathermy on reducing pain in low back pain at Haji Makassar General Hospital. The research design used was one group pretest-posttest, which involved 20 low back pain sufferers at Haji Makassar General Hospital who were selected by purposive sampling technique, with the criteria of not suffering from a fracture. Pain was measured using a numeric rating scale (NRS). Differences in the level of bacteria between before and after the intervention were analyzed using the Wilcoxon test. The results showed that the p-value was less than 0.05, meaning that there was a difference in pain levels between before and after the intervention. It was concluded that the muscle energy technique and microwave diathermy were effective in reducing pain levels in patients with low back pain.Keywords: muscle energy technique; microwave diathermy; pain level; low back pain ABSTRAK Low back pain adalah nyeri yang dirasakan pada daerah punggung bawah, dapat berupa nyeri lokal maupun nyeri radikuler atau keduanya. Penelitian ini bertujuan untuk mengetahui pengaruh muscle energy technique dan microwave diathermy terhadap penurunan nyeri pada low back pain di RSUD Haji Makassar. Rancangan penelitian yang digunakan adalah one group pretest-posttest, yang melibatkan 20 penderita low back pain di RSUD Haji Makassar yang dipilih dengan teknik purposive sampling, dengan kriteria tidak menderita fraktur. Nyeri diukur dengan menggunakan numeric rating scale (NRS). Perbedaan tingkat nteri antara sebelum dan sesudah intervensi dianalisis dengan uji Wilcoxon. Hasil penelitian menunjukkan nilai p kurang dari 0,05, artinya ada perbedaan tingkat nyeri antara sebelum dan sesudah intervensi. Disimpulkan bahwa muscle energy technique dan microwave diathermy efektif untuk menurunkan tingkat nyeri pada penderita low back pain.Kata kunci: muscle energy technique; microwave diathermy; tingkat nyeri; low back pain